Improvement of Electric Power System Efficiency and Control Over Their Operation while Using Flexible FACTS Transmission Systems - S. V. Kuzmitch; G. E. Pospelov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers a development of devices for increasing capacity and improvement of control over power lines of electric power systems in the CIS countries